Core-shell microparticles: Generation approaches and applications - Fariba Malekpour Galogahi (Journal of Science: Advanced Materials and Devices, 2020)
Micro-nanoscale core–shell particles are distinguishable from other particle types because of their unique composition. Core-shell particles combine the features of both the core and shell materials, while exhibiting smart properties resulting from their materials. In the past few years, the research community has paid increasing attention to the generation and application of core–shell structures. The present review focuses on the core–shell microparticles, which have found practical applications in various fields. The novel properties of the core–shell microparticles make them extremely suitable for pharmaceutical and biomedical applications, including cell encapsulation, cell study, targeted drug delivery, controlled drug release, food industry, catalysis, and environmental monitoring. This paper also systematically reviews the different classes of core–shell microparticles based on their respective materials. Moreover, an overview of conventional and more recent microfluidic methods for the generation of core–shell microparticles is presented. The unique advantages of the microfluidic approaches are highlighted.